Pengaruh Hedonic Shopping Motivation dan Fear of Missing Out (FOMO) terhadap Impulse Buying pada Konsumen Crocs di Kota Medan - Embun Tri Aulia; Mhd Aldy Khusairi R.; Nagita Suci Mahari; Sarif Halomoan Nasution; Onan Marakali Siregar; Ummi Salamah Sitorus (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
Amidst intense e-commerce competition in Indonesia, Shopee has emerged as a leading platform. However, with the continued addition of complex features, questions have arisen regarding the effectiveness of Perceived Ease of Use (PEOU) in shaping consumer intention to use. This study aims to examine this relationship in depth through a systematic literature review. The synthesis of results shows that PEOU significantly influences Intention to Use not only directly but also indirectly through two main mediating pathways: User Satisfaction and Consumer Trust. These findings confirm that PEOU remains a crucial factor even with new features. In conclusion, to maintain loyalty in a competitive market, Shopee must balance technical ease with emotional security to strengthen user trust and satisfaction. This study also shows that PEOU plays an equally important role in the technical and functional aspects of the platform. By enhancing an intuitive and accessible user experience, Shopee can ensure higher customer loyalty and encourage repeat purchase intentions. Furthermore, this study provides useful insights for platform developers to design more user-friendly features without neglecting the emotional aspects that also influence user decisions.